Implementasi Peraturan Pemerintah Nomor 53 Tahun 2010 Dalam Meningkatkan Disiplin Aparatur Sipil Negara di Dinas Pengendalian Penduduk dan Keluarga Berencana Kabupaten Tabanan - Ni Made Dwi Widari; Ni Nyoman Kartika Yanti (Universitas Warmadewa, 2025)
Government Regulation Number 53 of 2010 concerning Civil Servant (PNS) Discipline is the main guideline in regulating the discipline of State Civil Servants (ASN) in order to improve performance and professionalism in public services. This research aims to analyze the implementation of these regulations in improving ASN discipline in the Tabanan Regency Population Control and Family Planning Service and identify supporting and inhibiting factors in its implementation. This research uses a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The results of the research show that the implementation of Government Regulation Number 53 of 2010 in the Tabanan Regency Population Control and Family Planning Service has been quite effective, marked by increased ASN compliance with working hours, duties and responsibilities. However, there are still several obstacles, limited recruitment and regeneration of family planning instructors, limited budget, lack of community interest and motivation, heavy workload, wide area coverage, and limited facilities and supporting infrastructure. The supporting factors in implementing this regulation include the leadership's commitment to enforcing the rules, the existence of a clear system of rewards and sanctions, as well as strengthening supervisory mechanisms. With this regulation, the mechanism for monitoring and coaching employees can run more systematically through sanctions and rewards that are applied in accordance with the provisions. This is proven by an average attendance of 98%.